(untitled) (Bulletin KNOB, 1992)
The article focuses on architectural iconography, which is at the core of Aart Mekking’s inaugural address delivered at Leiden University. During the fifties this specialism gained popularity through the work of Günter Bandmann. Since then it has been limited by and large to the German-speaking world. Most studies in the field relate to Romanesque architecture. This may be due to the fact that here the separate parts of a building have a meaning in themselves, whereas in Gothic the concept of the building as a whole predominates, calling for an all-encompassing iconographical programme in the manner of Sedlmayr’s Gothic cathedral as the image of the Heavenly Jerusalem. However, the heyday of architectural allegory is in the Gothic period, witness Durandus of Wende’s Rationale (late thirteenth century). Another important difference is that Gothic building practice had become so complicated that it tended to obstruct the direct participation of the patron in the design process. Now he manifested himself above all in the decoration programmes for sculpture, stained glass, murals and liturgical props such as altarpieces. It is interesting to see Mekking apply, these problems notwithstanding, the method of architectural iconography to gothic architecture. His argument centers around the tower of Utrecht Cathedral (1321-1382). Referring to one of his earlier articles, he discovers two meanings in this tower: a secular one, i.e. symbol of the bishop’s sovereignty as a feudal lord, and a religious one as the symbol of the Heavenly Jerusalem to which the bishop guides his flock. Likewise, a series of more or less close imitations of this tower is iconographically explained on the basis of this twofold meaning. Mekking’s ideas, thought-provoking though they are, are not undebatable. First, architecture does not give a depiction, as a tympanum or an altarpiece does. Therefore the relation between what we see on the one hand and what it symbolically refers to on the other is more indirect than in the visual arts. In his previously published article Mekking has convincingly shown that within the iconographical context of the Ghent altarpiece the Utrecht tower signifies the Heavenly Jerusalem. This does not imply, however, that the tower itself, as it stands in Utrecht, has the same meaning. Moreover, both meanings are different in nature: the secular one is determined by specific political circumstances, the religious one is of a much more general character. Also in the case of the Amersfoort tower, strongly derived from Utrecht, there occurs this dissimilarity of meaning: according to Mekking this tower gained a concrete political meaning in the bishop’s struggle against the city of Utrecht, which refused to acknowledge him as their sovereign. This interpretation is based on the medieval allegorical exegesis of the Song of Songs. The problem, though, is that such an allegory is hardly applicable to very local and temporary conditions. Similar objections can be made for the other large towers dealt with (Rhenen, Groningen and Maastricht). With regard to the group of smaller brick towers around the city of Utrecht, formal characteristics are loaded with a concrete political significance without questioning whether these features were noticed as such in their own times. In Maastricht, finally, the octagonal lantern, derived from the Utrecht tower, is interpreted as the symbol of a strongly anti-Utrecht attitude. In doing so, the Middle Ages are reduced to a collection of symbolic signs, between which an all too modern relationship is constructed. However, Huizinga among others has shown that it is very common in those times to find thoughts and ideas at odds with the behaviour shown. In other words, even when a particular meaning can nowadays be constructed, this does not necessarily mean that it existed in the past. This criticism does not mean that the method of architectural iconography is in itself wrong. On the contrary, the concept that architectural forms are not chosen at random, but that they are open to historical explanation does make sense indeed. However, not only is it necessary to distinguish between intended meaning and meaning post festum, but also between two ways of reacting: on the one hand the direct reaction to some concrete event, on the other hand the way in which such an event is coped with symbolically - symbolical here conceived in the way E. Cassirer did. For especially in the case of architectural iconography there is only a diffuse - and for that very reason dangerous - border between speculation and acceptable hypothesis.